Students’ Perception toward Schema Theory That Used In Reading Class (A Study on the Fifth Semester Students of English Education Study Program of FKIP UNIB in Academic Year 2010/2011) - Risma Nurandini; Rudi Afriazi; Mulyadi Mulyadi (Universitas Bengkulu, 2017)
The objectives of this research are to identify the perception toward schema theory that used in reading class on the fifth semester students of English Education Study Program of FKIP UNIB in academic year 2010/2011. The population of this research was the fifth semester students of English Education Program of FKIP UNIB in academic year 2010/2011. The population of this study was the whole fifth semester students of English Study Program of Bengkulu University for academic year 2010 – 2011 which consist of 38 students. The sample of this study used total sampling technique. This study was a descriptive study. The instrument of this study was questionnaire. The questionnaire consists of 25 items that purpose to measure students’ perception toward schema theory. The result of this research show that the schema theory had 86,50% positive perception, 12,30% neutral perception and 1,20% negative perception. It displayed that the respondents had high positive perception toward schema theory. It means that most of the students agree with the application of schema theory as a learning style in the fifth semester students of English Education Program of FKIP UNIB in academic year 2010/2011.